2017
DOI: 10.1136/bmjopen-2017-017762
|View full text |Cite
|
Sign up to set email alerts
|

Key factors of case management interventions for frequent users of healthcare services: a thematic analysis review

Abstract: ObjectiveThe aim of this paper was to identify the key factors of case management (CM) interventions among frequent users of healthcare services found in empirical studies of effectiveness.DesignThematic analysis review of CM studies.MethodsWe built on a previously published review that aimed to report the effectiveness of CM interventions for frequent users of healthcare services, using the Medline, Scopus and CINAHL databases covering the January 2004–December 2015 period, then updated to July 2017, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 40 publications
1
62
0
4
Order By: Relevance
“…For all these reasons, recruiting a competent CM can be challenging, as is the case in other types of interventions oriented towards the care management of a complex clientele (Hudon et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…For all these reasons, recruiting a competent CM can be challenging, as is the case in other types of interventions oriented towards the care management of a complex clientele (Hudon et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous research, 60,[62][63][64] as well our prior thematic analysis review on key factors of CM interventions, 65 have recognized the importance of appropriate patient identification. Previous studies, however, have defined the appropriateness of patient identification on the basis of patients' risk of frequent health care use and associated cost to health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…Thorne and colleagues investigated everyday self-care decision making among persons with chronic illness, but who are not specifically frequent users 23. Numerous studies have shown that patient engagement in case management programs fosters successful interventions and can greatly improve patients' health status 11,[24][25][26]. On the other hand, this remains hard for a lot of patients since half of the patients involved in our study identified the decision "Do I acknowledge my condition and accept to be involved in its management?"…”
mentioning
confidence: 99%